Cooperative Learning Method Type Numbered Heads Together (Nht) Students In Efforts To Increase Liveliness And Materials Management Marketing Mastery In Economics Faculty Muhammadiyah University Of North Sumatra - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This research aims to enhance the activity of the students in the lecture courses marketing management in particular through the implementation of cooperative learning Numbered Heads Together (NHT) and to find out how far the mastery of course material marketing management with the implementation of cooperative learning Numbered Heads Together (NHT). This research is a classroom action research using cooperative learning strategies Numbered Heads Together (NHT). Data collection techniques in this research test methods in order to determine student results, the documentation which is to get important records related to the problem of learning, observation of the conduct of recording in behavior as a group or individually, interviews with the aim of revealing data on the implementation of lectures through a cooperative learning approach Numbered Heads Together (NHT). The data analysis used in this study with descriptive analysis. From the results of this research study marketing management using the type Numbered Heads Together (NHT) may enhance the activity and student mastery of the material.Keywords: Cooperative learning, learning Type Numbered Heads Together (NHT), the activity of students, mastery of the material